Patients' Perceptions of Homeopathic Consultations in an Integrative Care Day Hospital for Oncology Outpatients in Strasbourg, France: A Qualitative Study - Bagot, Jean-Lionel; Lilova, Mariya (Homeopathy, 2025)
Homeopathic consultations complement conventional medicine by emphasizing individualized and specific patient symptoms. While numerous studies have examined the efficacy of homeopathic treatments, very few have explored patients' experiences during these consultations.To analyze and understand how patients perceive this period of care, through a qualitative study conducted at the Integrative Care Day Hospital for oncology outpatients at Toussaint Hospital in Strasbourg, France.Using interpretative phenomenological analysis, we conducted semi-structured interviews between February and April 2022 with patients living with advanced cancer. Participants were referred by oncologists or supportive care providers to the hospital, where they received various integrative therapies, including homeopathy, acupuncture, aromatherapy, dietetics, osteopathy, mindfulness, art therapy, socio-aesthetic care, and psychological support. Interviews focused on patients' lived experiences. Data collection continued until thematic saturation was reached, which occurred after 20 anonymized interviews.Seventeen of the 20 patients spontaneously commented on the homeopathic consultations, revealing seven key themes: attentive listening; sufficient time; trust and understanding; a holistic and person-centered approach; clear and detailed explanations; open-minded dialogue; comprehensive clinical and paraclinical assessment. Consultations were perceived as moments of calm, openness and humanity. The care was described as non-intrusive, providing clarity and meaningful explanations.Findings align with prior qualitative research: homeopathic consultations in integrative oncology were positively received, appreciated for their holistic and empathetic nature. These results highlight the meaningful contribution of homeopathy in integrative oncology.
Keywords: homeopathy; patient satisfaction; physician–patient relationship; qualitative study; integrative oncology